Beispiel Nr: 09
$ \\ \text{Gegeben: Polynom vom Grad n } \\ \text{Gesucht: } \\ \text{Lösung der Gleichung} \\ $
$\textbf{Aufgabe:}$ $-\frac{1}{6}x^4+2x^2=0$
$\textbf{Rechnung:}\\ -\frac{1}{6}x^4+2x^2=0\\ x^2(-\frac{1}{6}x^2+2)=0 \Rightarrow x=0 \quad \vee \quad-\frac{1}{6}x^2+2=0\\ -\frac{1}{6}x^2+2 =0 \qquad /-2 \\ -\frac{1}{6}x^2= -2 \qquad /:\left(-\frac{1}{6}\right) \\ x^2=\displaystyle\frac{-2}{-\frac{1}{6}} \\ x=\pm\sqrt{12} \\ x_1=3,46 \qquad x_2=-3,46 \\ \underline{x_1=-3,46; \quad1\text{-fache Nullstelle}} \\\underline{x_2=0; \quad2\text{-fache Nullstelle}} \\\underline{x_3=3,46; \quad1\text{-fache Nullstelle}} \\$